Математичне моделювання траєкторії руху твердих частинок у вихрових камерах - Роговий, Андрій Сергійович; Rogovyi, Andrii; Тімченко, Є. І.; Timchenko, Ye.; Дьомін, Д. Р.; Domin, D.; Цента, Євген Миколайович; Tsenta, Yevhen (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: Метою роботи є розробка аналітичної моделі для визначення траєкторії руху твердої частинки у вихровій камері газового середовища з урахуванням сил лобового опору та градієнта тиску. Наукова новизна полягає у використанні аналітичного підходу для потенційного руху газу, що дозволяє оцінити вплив розміру та густини частинок на їх динаміку без значних обчислювальних витрат. Практична цінність дослідження полягає у можливості застосування отриманих результатів для оптимізації конструкцій вихрових клапанів, вихорокамерних нагнітачів у системах транспортування газових середовищ із твердими включеннями. Основні результати показують, що траєкторії частинок мають спіралеподібний характер, а час перебування залежить від їх розміру та густини; неврахування сили тиску може призвести до похибки до 60 %. Врахування градієнта тиску для дрібних частинок та перспективність аналітичного моделювання як бази для подальших досліджень підтверджується результатами моделювання траєкторій. /// EN: This paper presents an analytical approach to modeling the trajectory of solid particles in a vortex chamber operating within a gaseous medium. The primary objective is to develop a simplified yet accurate mathematical model that accounts for the main forces acting on a particle: drag and pressure gradient, while minimizing computational complexity compared to full-scale CFD simulations. The novelty of the study lies in applying potential flow theory to describe the gas motion and superimposing the particle’s movement on this flow, enabling rapid evaluation of particle dynamics under varying conditions. The methodology involves dividing the vortex chamber into four distinct regions: the mixing zone of supply and control flows, the central core, boundary layers on end walls, and the outlet region. The particle is assumed to be an ideal sphere with negligible concentration effects, and its trajectory is calculated using force balance equations solved by the Runge-Kutta method (4th-5th order) in MATLAB. Initial conditions include particle size, density, and inlet gas velocity, allowing parametric analysis of their influence on motion. Results indicate that particle trajectories form spirals with progressively decreasing radial increments, asymptotically approaching the chamber periphery. Larger and denser particles exhibit less curvature and shorter residence times, while smaller particles remain longer in the core region. Neglecting the pressure force introduces significant errors up to 60% for particles smaller than 20 μm highlighting the necessity of considering radial pressure gradients in design calculations. The practical significance of this research lies in its applicability to the optimization of vortex valves and flow control devices in pneumatic transport systems, particularly for gas-solid mixtures. The proposed analytical model provides a cost-effective tool for preliminary design and can serve as a foundation for further validation through advanced CFD techniques and experimental studies.
Mathematical modelling of the motion trajectory of solid particles in vortex chambers
Keywords: вихровий клапан; частинка; аналітичне моделювання; градієнт тиску; двофазний потік; газове середовище; вихорокамерний нагнітач; vortex valve; particle; analytical modeling; pressure gradient; two-phase flow; gaseous medium; vortex chamber amplifier